Pela estrada se vai com anseios no peito e pés no chão : por entre quereres e fazeres da (trans)formação ambiental na educação do campo - Modesto, Mônica Andrade (2019)
Rural education as an educational dimension and the education offered rurally, which has been becoming increasingly more invisible by curricular and pedagogical proposals subjugated to the interests of the capitalism, which regarded as educational dimension contributes to the environmental formation of the rural people. In this sense, this research aims to comprehend the curricular proposals present in the schools located in the rural area of Simão Dias-SE which can enable environmental education. The research is anchored in theoretical contributions of Critical Education and methodological procedures which provided the emerging perception of the curriculum and the pedagogical actions guiding the formative process of the researched context, focusing on environmental education. In order to attend this purpose, it was opted for the research the qualitative approach, which makes possible the interpretative analysis of the data that were produced through documentary analysis, the Referencial Curricular do Estado de Sergipe (Sergipe State Referential Curriculum), the Base Nacional Comum Curricular (National Common Base Curriculum), the books adopted by the municipal school system and the information contained in the questionnaires answered by the principals, coordinators and teachers of the schools composing the research sample, and semistructured interviews with the effective teachers enrolled in the sample. The data were analyzed towards the Discourse Analysis and pointed the predominance of an environmental education guided by the naive conception of education, reverberated, in this regard, in the conceptions related to rural education and environmental education and by simplistic pedagogical actions concerning the research object which nevertheless, in some extent, presented potentialities to the promotion of environmental formation in the locus here investigated. At the end, possibilities for the development of pedagogical praxis directed to teacher training in the perspective of environmental education are listed, given the fact the instructional deficit of the researched subjects was the aspect that presented greater fragility and interference in the identified results. In this view it is expected to contribute to the fields of rural education and the environmental education with this study, raising theoretical reflections about their assumptions and new research problems, as well as for the improvement of the formation process offered to rural children in the state of Sergipe and in the municipality of Simão Dias.